2021
DOI: 10.3390/jcm10030474
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Rotational Osteotomies around the Patellofemoral Joint

Abstract: Torsional abnormalities of the femur represent a significant risk factor for patellar instability or patellofemoral complaints. Although their clinical implication has been demonstrated, there is still a debate going on about different aspects. These include, especially, the various methods of measurements with a wide range of physiologic values, the indication or clear recommendation for surgical correction, and the site of the rotational osteotomy. Nevertheless, good subjective and objective functional resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Increased FA could cause a laterally directed force vector acting on the patella, which might increase pressure on the reconstructed MPFL and even result in graft failure and patellar re‐dislocation [16, 26, 29], accompanied by increased contact stress on the lateral patellofemoral joint, abnormal gait pattern, increased TT–TG distance, and dysplastic trochlea [2, 3, 15, 21, 29]. Therefore, performing DDFO to reduce increased FA should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Increased FA could cause a laterally directed force vector acting on the patella, which might increase pressure on the reconstructed MPFL and even result in graft failure and patellar re‐dislocation [16, 26, 29], accompanied by increased contact stress on the lateral patellofemoral joint, abnormal gait pattern, increased TT–TG distance, and dysplastic trochlea [2, 3, 15, 21, 29]. Therefore, performing DDFO to reduce increased FA should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 12 , 22 , 24 , 25 In addition, previous studies failed to offer a suitable femoral level for osteotomies. 2 , 5 , 20 , 26 In the present study, we compared the differences in femoral torsion between patients with patellar dislocation and healthy individuals. The results of our study showed that excessive femoral torsion most frequently presented in the total, mid, and distal femoral segments in patients with patellar dislocation ( P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, derotational femoral osteotomy has been proposed as an alternative therapy for RPD with increased femoral anteversion to eliminate the adverse influences of torsional deformity on the patellofemoral joint, and this outcome has been demonstrated in recent clinical studies. 2,3,7,8,10,13,23 In a recent systematic review, Zhang et al 33 investigated the role of derotational distal femoral osteotomy (DDFO) in treating RPD with increased femoral anteversion and found that DDFO led to favorable clinical outcomes with a low redislocation rate.…”
mentioning
confidence: 99%